2022
DOI: 10.3390/pharmaceutics14010179
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assimilation of CuS, Iron Oxide and Iron Oxide@CuS Nanoparticles in Mice: A 6-Month Follow-Up Study

Abstract: Nanoparticles (NPs) are at the leading edge of nanomedicine, and determining their biosafety remains a mandatory precondition for biomedical applications. Herein, we explore the bioassimilation of copper sulfide NPs reported as powerful photo-responsive anticancer therapeutic agents. The nanoparticles investigated present a hollow shell morphology, that can be left empty (CuS NPs) or be filled with an iron oxide flower-like core (iron oxide@CuS NPs), and are compared with the iron oxide nanoparticles only (iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Hence, the blood residence time of the MNPs appears to be less than 7 days irrespective of the coating they carry. In fact, 7 days after administration the MNPs had accumulated in the different organs in which they were distributed [ 36 , 57 , 58 ], which led us to analyze the biodistribution of all the MNPs at this time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the blood residence time of the MNPs appears to be less than 7 days irrespective of the coating they carry. In fact, 7 days after administration the MNPs had accumulated in the different organs in which they were distributed [ 36 , 57 , 58 ], which led us to analyze the biodistribution of all the MNPs at this time.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies that monitored the bioassimilation of empty copper sulfide NPs (CuS-NPs) or NPs with a flower-like core of iron oxide (iron oxide@CuS-NPs) finally coated with PEG, showed their accumulation mainly in the liver and spleen following i.v. administration to 6-week-old Balb/C mice [ 96 ]. Regarding the degradation of these particles up to 6 months post-administration, they appeared to remain intact within the liver and spleen in TEM images for up to 7 days post-administration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were reported in a mouse model in which 70 µg of iron oxide nanoparticles were injected intravenously, and serial transmission electron microscopy showed progressive degradation of the particles. An in vivo study showed that the liver reserve of iron increased after the IV IOP injection and returned to standard levels 180 days later [ 38 ]. We found that MR images are a powerful in vivo tool for evaluating iron reserves.…”
Section: Discussionmentioning
confidence: 99%